The Unfolded Protein Response and the Role of Protein Disulfide Isomerase in Neurodegeneration - Perri, Emma R.; Thomas, Colleen J.; Parakh, Sonam; Spencer, Damian M.; Atkin, Julie D. (Frontiers in Cell and Developmental Biology, 2016)
The maintenance and regulation of proteostasis is a critical function for post-mitotic neurons and dysregulation of proteostasis is increasingly implicated in neurodegenerative diseases. Despite having different clinical manifestations, these disorders share similar pathology; an accumulation of misfolded proteins in neurons and subsequent disruption to cellular proteostasis. The endoplasmic reticulum (ER) is an important component of proteostasis, and when the accumulation of misfolded proteins occurs within the ER, this disturbs ER homeostasis, giving rise to ER stress. This triggers the unfolded protein response (UPR), distinct signalling pathways that whilst initially protective, are pro-apoptotic if ER stress is prolonged. ER stress is increasingly implicated in neurodegenerative diseases, and emerging evidence highlights the complexity of the UPR in these disorders, with both protective and detrimental components being described. Protein Disulphide Isomerase (PDI) is an ER chaperone induced during ER stress that is responsible for the formation of disulphide bonds in proteins. Whilst initially considered to be protective, recent studies have revealed unconventional roles for PDI in neurodegenerative diseases, distinct from its normal function in the UPR and the ER, although these mechanisms remain poorly defined. However specific aspects of PDI function may offer the potential to be exploited therapeutically in the future. This review will focus on the evidence linking ER stress and the UPR to neurodegenerative diseases, with particular emphasis on the emerging functions ascribed to PDI in these conditions.